CYTOPROTECTOR MILDRONATE IN CORRECTING MYOCARDIAL DYSFUNCTION AMONG STABLE ANGINA PATIENTS AFTER CORONARY REVASCULARISATION - I. G. Gordeev; E. E. Luchinkina; S. V. Hegay (Российский кардиологический журнал, 2009)
In total, 149 patients, aged 41–75 years, with Functional Class (FC) II-III stable angina, who underwent coronary artery bypass graft surgery (CABG) or percutaneous coronary intervention (PCI), were examined. Group I (n=79) received standard therapy, as well as post-intervention mildronate therapy (750 mg/day for three days, then 750 mg per day twice a week). Group II (79 controls) did not receive any metabolic medications. Total and local left ventricular (LV) myocardial contractility was assessed by echocardiography 10–15 days before, 2–3 days before, and 10–12 days after the revascularisation. Mildronate therapy was associated with total and local myocardial contractility improvement, observed even before the intervention and further increasing after the operation. It was also linked to the reduction in post-revascularisation, reperfusionrelated LV myocardial dysfunction.